Hubungan Antara Kadar Feritin Dengan Kadar ALT dan AST Pada Pasien Thalasemia di RSUD Dr. Moewardi - Prabandari, Valentina Lakhsmi; Riza, Muhammad; Wijayanti, Lilik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Thalassemia major patients need a regular blood transfusion that may cause an iron overload and vital organ dysfunction. This was an observational analytic study to analyze the relationship between ferritin level and transaminase enzymes level in thalassemia patients at Dr.Moewardi General Hospital. A positive relation may remind doctor to pay attention of liver function in thalassemia major patients. Methods: The research was an observational analytic study with cross sectional approach during April-June 2013 in Dr. Moewardi General Hospital. The samples was taken using exhaustive sampling and all were children with beta thalasemia major. These patients had a regular blood transfusion, high ferritin level (>1000 ng/l) and iron chelating agents usage. Ferritin level as independent variable was measured with ELFA method. Transaminase enzymes as dependent variables were measured with IFCC method. These variables were analyzed with Pearson correlation, diagnostic odds ratio and linier regression. Results: Thirty thalassemia patientsâ test results of ferritin, ALT and AST level were collected. Eighteen patients had a very high ferritin level (â¥3000 ng/l) and the other twelve patientsâ ferritin level were between 1000-3000 ng/l. Eighteen patients had a high ALT level and seventeen patients had a high AST level. Pearson analysis showed a significant result between ferritin and ALT level (p=0.043) also between ferritin and AST level (p=0.028). Pearson correlation strengths were moderate (0.373 and 0.401). Odds ratio between ferritin level with ALT and AST level were 3.333 and 3.111. Conclusions: There was a positively moderate correlation between ferritin level and both ALT and AST level in thalassemia patients in Dr. Moewardi General Hospital. Odds ratio analysis showed that ferritin level above 3000 ng/l is a risk factor of ALT and AST level elevation. Keywords: Thalassemia, iron overload, ferritin, transaminaseÂ